Derivational Nominal Suffixes In Selected Speech From Barack Obama - Ni Luh Putu Ari Permata Dewi; I Nyoman Sedeng; I Gusti Ngurah Parthama (CV. Ulil Albab Corp, 2023)
This study aims to analyze derivational nominal suffixes in selected speech from Barack Obama. The official website of the White House President Barack Obama published the speech on 21 January 2009 and 3 October 2002. To determine the functions of the derivational suffixes using the theory proposed by Plag (2002) and the definitions of morpheme, morphological process, root, stem and base, and suffix were identified using the theory by Katamba (1993). This study identified the functions of derivational suffixes, which are Class Maintaining Suffixes and Class Changing Suffixes, and their word structures. The data collected in this study was explained in words using qualitative methods. The findings showed that there are 15 data on the functions of derivational suffixes found in the selected speech from Barack Obama, 5 data classified as a class maintaining derivational suffix and 10 data are kind of class-changing derivational suffixes.